Validating a Nursing Assessment instrument in a Pediatric Intensive Care Unit - Gomes Correa, Aline Medianeira; Tavares, Daniel Soares; Garcia de Lima Parada, Cristina Maria [UNESP]; Pereira, Adriana Dall'Asta; Mancia, Joel Rolim; Backes, Dirce Stein (Assoc Brasileira Enfermagem, 2020)
Objective: To develop and validate a Nursing History instrument for a Pediatric Intensive Care Unit, based on the Theory of Basic Human Needs. Methods: Methodological study, developed between October 2018 and April 2019, based on the establishment of a theoretical-conceptual structure; construction of items and of the response scale; selection and organization of items; structuring the instrument; expert opinion; and content and appearance validation. Results: The instrument was organized in three sequential and complementary stages. The first stage considered data collection; the second, the collection of additional information, like Psychobiological, Psychosocial and Psychospiritual Needs; and the third collected data related to a physical examination. The instrument had good internal consistency (0,75) and an agreement percentage equal to or greater than 0,83. Conclusion: The Nursing History instrument developed and validated here can be considered relevant and pertinent in terms of content, clarity, scope, and appearance.
Keywords: Nursing; Validation Studies; Nursing Process; Child Health; Intensive Care Units; Pediatric